Teacher-Student Relationship and Teacher Subjective Well-being: Understanding the Employment Status as Moderator - Nugraha, Akhmad Yazid; Saleh, Airin Yustikarini; Safitri, Shahnaz (Jurnal Pendidikan Progresif, 2023)
Teacher-Student Relationship and Teacher Subjective Well-being: Understanding the Employment Status as Moderator. Objective: This research aimed to see whether the teacher employment status could moderate the association between teacher-student relationship and teacher subjective well-being in secondary level of education. Methods: This study uses a quantitative research approach with a non-experimental correlational design. Correlation analysis and simple regression analysis was used to measure the moderation effect. Findings: The result showed that no significant moderation effect of the employment status on the effect of teacher-student relationship to the teacher subjective well-being. Conclusion: The findings of this study fail to confirm the moderation effect of employment status on the association between teacher-student relationship and teacher subjective well-being in secondary level of education.  Keywords: teacher subjective well-being; teacher-student relationship; teacher employment status; secondary schools.DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202304